Trends in Brazilian regulation of business - Rosenn, Keith S. ([Washington, D.C.] : American Enterprise Institute for Public Policy Research, Center for Hemispheric Studies, 1981)
A project work on the role of the state in the political economy of Latin America and on the interconnection between Liberia. It is a study of state-society relations focused particularly on state regulation of labour and entrepreneurial groups in Lain America.
Cover title.
Includes bibliographical references.
sju 25/01/2019
Loans
Keywords: Industrial laws and legislation